2020
DOI: 10.1002/iid3.341
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing noncoding RNA‐based macrophage polarization: Emerging therapeutic opportunities for fibrosis

Abstract: Aim Organ fibrosis is a common pathological outcome of persistent tissue injury correlated with organ failure and death. Although current antifibrotic therapies have led to unprecedented successes, only a minority of patients with fibrosis benefit from these treatments. There is an urgent need to identify new targets and biomarkers that could be exploited in the diagnosis and treatment of fibrosis. Methods Macrophages play a dual role in the fibrogenesis across different organs either by promoting pro‐inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The functions of circRNAs are different according to their localization in cells [30,31]. Most circRNAs molecules are localized in the cytoplasm and exert effects by RNA-RNA interactions including sponging with miRNAs and antagonizing their posttranscriptional regulatory effects on the downstream mRNAs [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of circRNAs are different according to their localization in cells [30,31]. Most circRNAs molecules are localized in the cytoplasm and exert effects by RNA-RNA interactions including sponging with miRNAs and antagonizing their posttranscriptional regulatory effects on the downstream mRNAs [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs, a novel class of endogenous non coding RNAs, are widely expressed in mammals. By regulating macrophage polarization, circRNA plays a key role in many diseases, such as tumor [ 24 ], type 1 diabetes mellitus (T1DM) [ 25 ], and fibrosis [ 26 ]. Hsa_circ_0005567 is a new osteoarthritis-related circRNA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, miR-140 was reported with a key protective role against RILF by inhibiting myofibroblast differentiation and inflammation, and its loss was suggested to induce lung fibrosis through reprogramming fibroblasts and M2 macrophages ( 76 ). The role of non-coding RNAs in modulating macrophage phenotypic plasticity and functional heterogeneity among different fibrotic diseases has been recently reviewed ( 77 ). These reports further highlight the plausible role of macrophage-derived microRNAs in PF.…”
Section: Microrna-based Regulation Of Macrophage Polarization In Immune Response Inflammation and Fibrosismentioning
confidence: 99%